Breaking the Cycle: Reforming Child Support Debt and Employment Barriers for Incarcerated Parents - Nicholas A Ciborowski; Cynthia L Miller (Undergraduate Research Journal for the Human Sciences, 2025)
This policy brief examines the challenges faced by incarcerated and formerly incarcerated individuals in managing child support debt while navigating financial and employment disparities. Research indicates that up to 85% of incarcerated men have child support obligations, with some states reporting rates as high as 100% (May, 2017). The rapid accumulation of debt during incarceration and the limited post-release earning potential contribute to cycles of economic instability, family disruption, and recidivism. This brief presents evidence-based policy recommendations to address these challenges, including debt restructuring and suspension programs, enhanced vocational and employment support, a shift from punitive to rehabilitative enforcement strategies, improved data collection for targeted policy solutions, and greater investment in family support services. Implementing these reforms can help policymakers promote economic self-sufficiency, strengthen family relationships, and create a more supportive and equitable system for affected families.
Keywords: child support reform; incarceration and employment; reentry barriers; family stability; criminal justice policy